Fractional order capacitors - Jesus, Isabel S. (2019)
The performance of electrical devices, depending on the processes of the electrolytes, have been fully described and the physical origin of each parameter is well established. However, the influence of the irregularity of the electrodes was not a subject of study and only recently, this problem became relevant in the viewpoint of fractional calculus. This paper describes an electrolytic process in the perspective of fractional order capacitors. In this line of thought, are developed several experiments for measuring the electrical impedance of the devices. The results are analyzed through the frequency response, revealing capacitances of fractional order that can constitute an alternative to the classical integer order elements.